Spectral and spatial selectivity of luminance vision in reef fish - Siebeck, Ulrike E.; Wallis, Guy Michael; Litherland, Lenore; Ganeshina, Olga; Vorobyev, Misha (Frontiers in Neural Circuits, 2014)
Luminance vision has high spatial resolution and is used for form vision and texture discrimination. In humans, birds and bees luminance channel is spectrally selective – it depends on the signals of the long-wavelength sensitive photoreceptors (bees) or on the sum of long- and middle- wavelength sensitive cones (humans), but not on the signal of the short-wavelength sensitive (blue) photoreceptors. The reasons of such selectivity are not fully understood. The aim of this study is to reveal the inputs of cone signals to high resolution luminance vision in reef fish. 16 freshly caught damselfish, Pomacentrus amboinensis, were trained to discriminate stimuli differing either in their colour or in their fine patterns (stripes vs. cheques). Three colours (‘bright green’, ‘dark green’ and ‘blue’) were used to create two sets of colour and two sets of pattern stimuli. The ‘bright green’ and ‘dark green’ were similar in their chromatic properties for fish, but differed in their lightness; the ‘dark green’ differed from ‘blue’ in the signal for the blue cone, but yielded similar signals in the long-wavelength and middle-wavelength cones. Fish easily learned to discriminate ‘bright green’ from ‘dark green’ and ‘dark green’ from ‘blue’ stimuli. Fish also could discriminate the fine patterns created from ‘dark green’ and ‘bright green’. However, fish failed to discriminate fine patterns created from ‘blue’ and ‘dark green’ colours, i.e. the colours that provided contrast for the blue-sensitive photoreceptor, but not for the long-wavelength sensitive one. High resolution luminance vision in damselfish, Pomacentrus amboinensis, does not have input from the blue-sensitive cone, which may indicate that the spectral selectivity of luminance channel is a general feature of visual processing in both aquatic and terrestrial animals.